Improving research personnel's hand hygiene adherence in the pediatric acute care setting during the COVID-19 pandemic: a quality improvement initiative. Issue 6 (18th November 2022) - Dissanayake, Ashini; MacLellan, Abigale; Doan, Quynh; Sabhaney, Vikram; Virk, Punit
Abstract : Introduction: Hand hygiene is critical in preventing the spread of healthcare-associated infections. Routine hand hygiene surveillance and education are common for clinical staff in pediatric acute care settings. However, nonclinical staff, including research personnel, are often excluded from these programs and therefore represent a gap in ongoing infection control efforts. This project aimed to evaluate the impact of evidence-based interventions on improving hand hygiene adherence among research personnel in the pediatric emergency department to meet provincial targets set for clinical staff. Methods: We used a Plan-Do-Study-Act approach to carry out a peer-driven, multimodal hand hygiene improvement strategy involving education, surveillance, and feedback targeted to research assistants working in a pediatric emergency department. Two anonymous peer evaluators observed hand hygiene practices in several specific instances (eg, before/after patient interactions) and determined adherence a priori. Results: In an open sample of clinical research assistants (Ntotal = 22), hand hygiene adherence increased from 12.5% to 89.1% over 11 months. Increases in adherence were particularly notable before entering the patient environment compared to exiting. Conclusions: Hand hygiene interventions targeting research personnel show potential success in acute care. Further quality improvement initiatives in larger research personnel samples must robustly evaluate the framework's effectiveness.